Root, rhizome and scape anatomy of Amazonian species of Mapania Aubl. (Mapanioideae, Cyperaceae) and its taxonomic and ecological significance - Silva, Arthur de Lima [UNESP]; Alves, Marccus Vinícius da Silva; Coan, Alessandra Ike [UNESP] (Wiley, 2019)
Cyperaceae are a cosmopolitan Monocot family comprising about 5,700 species divided into two subfamilies: Cyperoideae and Mapanioideae. Within Mapanioideae, Mapania is the largest genus, with about 90 species. Anatomical studies on Mapanioideae are of great importance but still scarce. Here, the anatomy of roots, rhizomes and scapes of five Amazonian species of Mapania is studied. The species have two types of roots, which differ anatomically: thick roots, serving mainly for fixing, and thin ones, mainly for nutrient absorption. Rhizomes show a uniform anatomical pattern, with amyloplasts and phenolic idioblasts in the cortex and in the vascular cylinder, without aerenchyma. In this organ, the collateral vascular bundles are similar to those found in Hypolytrum, a genus closely related to Mapania within Mapanioideae, suggesting that this feature may be diagnostic for the tribe Hypolytreae. The scape anatomy of the species is taxonomically important at species level but does not corroborate precisely the infrageneric classification of the genus. Finally, the aerenchyma found in roots and scapes is an adaptive character state for a humid forest environment. This work contributes valuable information for the anatomical characterization of vegetative organs of Mapania and discusses its taxonomic and ecological relevance.
Keywords: Hypolytreae; M. sect. Mapania; M. sect. Mapaniopsis; M. sect. Pycnocephala; Poales